The Tribal Rites of Specialists in Training - Bosk, Charles L. (The Hastings Center report, 1981)
Book reviewed in this article: Becoming Psychiatrists. By Donald Light Men Who Control Women's Health: The Miseducation of Obstetrician-Gynecologists. By Diana Scully